Research progress on Brassicaceae plants: a bibliometrics analysis - Zhou, Ruixue; Qin, Xinsheng; Hou, Junjun; Liu, Yining (Frontiers in Plant Science, 2024)
The Brassicaceae is a worldwide family that produces ornamental flowers, edible vegetables, and oilseed plants, with high economic value in agriculture, horticulture, and landscaping. This study used the Web of Science core dataset and the CiteSpace bibliometric tool to quantitatively visualize the number of publications, authors, institutions, and countries of 3139 papers related to Brassicaceae plants from 2002 to 2022. The keywords and references were divided into two phases: Phase 1 (2002-2011) and Phase 2 (2012-2022) for quantitative and qualitative analysis. The results showed: An average annual publication volume of 149 articles, with an overall fluctuating upward trend; the research force was mainly led by Professor Ihsan A. Al-shehbaz from Missouri Botanical Garden; and the United States had the highest number of publications. In the first phase, research focused on the phylogeny of Brassicaceae plants, while the second phase delved into diverse research based on previous studies, research in areas such as polyploidy, molecular technique, physiology, and hyperaccumulator has been extended. Based on this research, we propounded some ideas for future studies on Brassicaceae plants and summarized the research gaps.